The Use Of Alternative Stain In Rose Bengal Test Antigen Preparation Which Specific For Brucellosis. - Erada A .J . Saeed (The Iraqi Journal of Veterinary Medicine, 2006)
The Rose Bengal test is one of the famous diagnostic test of Brucellosis specially as a screening test in order to detect the infection in limited area. Rose Bengal standard stain which producd by specific companies was used in preparation of the test special antigen , The stain gives the known pink colour for the antigen during the test that make the agglutination in positive cases more visible due to the reaction between antigen and the specific antibodies of Brucella which found in the serum sample of human and different animals. Antigen for the Rose Bengal test in this study is prepared by using alternative stain easily found in local supermarkets using for food colours and not expensive like standard stain. All standard tests were down for the stain like the colour ,pH, stability are same for two stains until the date of expire of antigen. The antigen prepared with alternative stain was used in comparative with the antigen prepared with standard stain for testing serum samples of human and different animals, the results deal no significant different statistically between them that means as a result we can prepare antigen more easily and not expensive.